2007
DOI: 10.1021/jf0710534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Consumption of Organically and Conventionally Produced Apples on Antioxidant Activity and DNA Damage in Humans

Abstract: The present study was performed to compare the effects on antioxidant activity and on DNA damage of organic and conventionally produced apples grown under controlled conditions in human peripheral blood lymphocytes. Six healthy volunteers consumed either organically or conventionally grown apples (Golden Delicious, 1000 g) from two neighboring commercial farms in a double-blinded, randomized, cross-over study. The average content of total identified and quantified polyphenols in the organically and conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 34 publications
2
36
1
Order By: Relevance
“…These findings suggest that the consumption of whole apple provides a useful dietary source of active scavengers to protect cells and tissue from oxidative stress and related DNA injury. A protective effect exerted by apple intake on lymphocyte DNA has been observed by Brivida et al [70]. Vieira et al [71] confirmed that acute consumption of apple juice (AJ) of 2 Brazilian cultivars (Golden Delicious and Catarina) with different content of sugars, ascorbic acid, phenols, and antioxidant capacities exert an effect on the antioxidant status and serum lipid peroxidation (lipid hydroperoxides and thiobarbituric acid-reactive substances, TBARS) in humans.…”
Section: Oxidative Stressmentioning
confidence: 82%
“…These findings suggest that the consumption of whole apple provides a useful dietary source of active scavengers to protect cells and tissue from oxidative stress and related DNA injury. A protective effect exerted by apple intake on lymphocyte DNA has been observed by Brivida et al [70]. Vieira et al [71] confirmed that acute consumption of apple juice (AJ) of 2 Brazilian cultivars (Golden Delicious and Catarina) with different content of sugars, ascorbic acid, phenols, and antioxidant capacities exert an effect on the antioxidant status and serum lipid peroxidation (lipid hydroperoxides and thiobarbituric acid-reactive substances, TBARS) in humans.…”
Section: Oxidative Stressmentioning
confidence: 82%
“…Four of the 12 studies included in the review (33%) met the predefined quality criteria (12,17,18,22), 7 studies failed to specify the certification body under which the organic foodstuffs that were studied were produced (11, 13-16, 19, 20), and one publication did not provide sufficient information on the nature of the organic foodstuff under investigation (21). In the largest human study conducted to date, the proxy-reported consumption of strictly organic dairy products was associated with a reduced risk of proxy-reported eczema in infants (15).…”
Section: Overview Of Studies Identifiedmentioning
confidence: 99%
“…The remaining 4 studies hypothesized that agricultural production methods differentially affect markers of carcinogenesis (12) or the bioavailability of carotenoids (17) or polyphenolic substances (14,18).…”
Section: Study Hypothesesmentioning
confidence: 99%
“…Organic apples contained higher concentrations of hydroxycinnamic acids, flavanols, dihydrochalcones, querce- tins and total phenolics than apples from integrated cultivation (Mikulic Petkovsek et al 2010). Some studies have demonstrated no differences in the total phenolic content or in the classes of polyphenols between apples produced by organic and conventional/integrated methods (Briviba et al 2007;Peck et al 2009;Valavanidis et al 2009). …”
Section: Resultsmentioning
confidence: 99%